FACTORS INFLUENCING CONSUMER INTENTION TO PURCHASE REMANUFACTURED PRODUCTS WITHIN THE VIETNAMESE CIRCULAR ECONOMY - Thi Hoang Yen Le; Thanh Cong Nguyen; Duong Cam Phan; Thao Nguyen Nguyen; Van Duy Nguyen (Tạp chí Khoa học Đại học Đà Lạt, 2025)
This study extends the theory of planned behavior (TPB) by incorporating environmental knowledge, environmental beliefs, and perceived value to understand Vietnamese consumer purchase intentions towards remanufactured products. The research aims to offer insights that support Vietnam’s transition towards a circular economy. Data were collected from 277 respondents using a structured survey, which assessed the relationships between environmental knowledge, beliefs, attitudes, perceived value, social pressure, product availability, and purchase intentions. Partial least squares structural equation modeling (PLS-SEM) was employed to analyze the hypothesized relationships. The results show that attitude has the strongest positive influence on purchase intention, driven primarily by environmental beliefs and knowledge. Additionally, product availability also significantly impacts purchase intention. The findings emphasize the importance of knowledge dissemination and product accessibility in fostering sustainable consumption behaviors. These insights suggest that policymakers and businesses should prioritize strategies that increase environmental knowledge, foster positive attitudes towards remanufactured products, and ensure their accessibility, thereby promoting sustainable consumption habits and advancing the circular economy in Vietnam.